THE EFFECT OF INVESTMENT DECISION AND PROFITABILITY TO COMPANY VALUE IN MANUFACTURING COMPANY INDUSTRIAL SECTOR CONSUMPTED GOODS REGISTERED IN INDONESIA STOCK EXCHANGE YEAR 2012 - 2016 - Ompusunggu, Hermaya Maya (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
This research has purpose to know influence of investment decision and profitability to company value. The method used is multiple linear regression, t test and f test. Based on the results of research that has been described statistically with SPSS program from the test result Investment Decision variable shows the significance value of 0.000 which is smaller than 0.05 which means Investment Decision variable partially affect the variable Company Value and test results t variable Profitability shows the significance value 0.000 which is smaller than 0.05 which means the variable Profitability partially affect the variable Value Company. Based on the results of research that has been statistically described by using SPSS program from F test shows that the value of F arithmetic variable of Investment Decision and Profitability variable with significant 0.000 and smaller than 0.05 which means Investment Decision and Profitabilitias simultaneously affect the Company Value